Action potential variability in human pluripotent stem cell-derived cardiomyocytes obtained from healthy donors - Carvalho, A. B.; Coutinho, Keyla Cristiny da Silva; Barbosa, Raiana Andrade Quintanilha; Campos, Dilza Balteiro Pereira de; Leitão, Isabela de Carvalho; Pinto, R. S.; Dos Santos, D. Silva; Farjun, Bruna; De Araújo, Dayana da Silva; Mesquita, Fernanda Cristina Paccola; Monnerat-Cahli, G.; Medei, E. H.; et al. (Frontiers in Physiology, 2022)
Human pluripotent stem cells (PSC) have been used for disease modelling, after differentiation into the desired cell type. Electrophysiologic properties of cardiomyocytes derived from PSC are extensively used to model cardiac arrhythmias, in cardiomyopathies and channelopathies. This requires strict control of the multiple variables that can influence the electrical properties of these cells. In this article, we report the action potential variability of 780 cardiomyocytes derived from PSC obtained from 6 healthy donors. We analyze the overall distribution of action potential (AP) data, the distribution of AP data per cell line, per differentiation protocol and batch. This analysis indicates that even using the same cell line and differentiation protocol, the differentiation batch still affects the results. This variability has important implications in modeling arrhythmias and imputing pathogenicity to variants encountered in patients with arrhythmic diseases. We conclude that even when using isogenic cell lines to ascertain pathogenicity to variants associated to arrythmias one should use cardiomyocytes derived from PSC using the same differentiation protocol and batch and pace the cells or use only cells that have very similar spontaneous beat rates. Otherwise, one may find phenotypic variability that is not attributable to pathogenic variants.